STRATEGI BANK SYARIAH MANDIRI DALAM MENINGKATKAN PEMAHAMAN TENTANG PRODUK PEMBIAYAAN MUDHARABAH (STUDI PADA MASYARAKAT KECAMATANTAMBUN SELATAN, KABUPATEN BEKASI) - Agus Sudradjat (Jurnal Manajemen FE-UB, 2022)
The purpose of this study is to find out how the strategy of Bank Syariah Mandiri in increasing public understanding of mudharabah financing products (Study on the people of South Tambun District - Bekasi Regency) and to find out the factors that cause people in the South Tambun District area not to understand mudharabah financing. In depth and comprehensively, the researcher used a qualitative descriptive approach with primary data collection techniques and secondary data in the form of observation, interviews, and documentation. The data obtained were analyzed using the Miles and Huberman Model. From the results of the study, it was found that the strategy in increasing understanding carried out by Bank Syariah Mandiri Bekasi Regency to the people of South Tambun District about mudharabah financing was using socialization, education, and door prizes/gifts with media such as socialization, saleskits, telemarketing. The factor causing the lack of public understanding of mudharabah financing is because the people of South Tambun District belong to traditional communities that require a special approach so that people can easily understand mudharabah financing. Keywords: Understanding, Mudharabah Financing, CommunityThe purpose of this study is to find out how the strategy of Bank Syariah Mandiri in increasing public understanding of mudharabah financing products (Study on the people of South Tambun District - Bekasi Regency) and to find out the factors that cause people in the South Tambun District area not to understand mudharabah financing. In depth and comprehensively, the researcher used a qualitative descriptive approach with primary data collection techniques and secondary data in the form of observation, interviews, and documentation. The data obtained were analyzed using the Miles and Huberman Model. From the results of the study, it was found that the strategy in increasing understanding carried out by Bank Syariah Mandiri Bekasi Regency to the people of South Tambun District about mudharabah financing was using socialization, education, and door prizes/gifts with media such as socialization, saleskits, telemarketing. The factor causing the lack of public understanding of mudharabah financing is because the people of South Tambun District belong to traditional communities that require a special approach so that people can easily understand mudharabah financing. Keywords: Understanding, Mudharabah Financing, Community